Literacy in the New Media Age: What Has Changed ? - Dahal, Sudhamshu (Bodhi: An Interdisciplinary Journal, 2024)
Media landscape has seen remarkable changes over the decades because of new technological inventions globally. Technological inventions have multiple impacts in media landscape that has been differently shaping the traditional one-way communication practice. The concept of media literacy interpreted earlier has also been shifting, and there are issues with the arrival of new interactive media in the world. This article deals with media literacy: its basic concepts and theoretical assumptions and the shifting of the traditional definition guided by the changing media technology and media consumption pattern in Nepali context. It examines the changing Nepali media literacy landscape through a critical approach and analyze how the content generation has been impacted by the changing media climate.